Certain Subclasses of Meromorphic Functions Involving Differential Operator - Hameed, Ismael I.; Juma, Abdul Rahman S. (Iraqi Journal of Science, 2022)
We obtain the coefficient estimates, extreme points, distortion and growth boundaries, radii of starlikeness, convexity, and close-to-convexity, according to the main purpose of this paper.